Technologies of physical and chemical impact on potato planting material - A. K. Zinoviev; G. K. Rembalovich,; M. Yu. Kostenko (Сельскохозяйственные машины и технологии)
The paper highlights that it is planned to increase the cultivation area of open ground vegetables and potatoes for ensuring the food security. (Research purpose) This study aims to explore methods and technologies for pre-planting treatment of potatoes. (Materials and methods) The research was conducted in the Tula region where Rannee Utro (Early Morning) and Rokko potato varieties were studied under natural infectious conditions. Various fungicides and biological products containing different active ingredients were applied to protect potatoes. Additionally, the study investigated the eff ects oflow-pressure mercury ultraviolet discharge lamps and magnetic field treatments on the biopotential and pH levels of potatoes. (Results and discussion) The study focuses on enhancing potato yields by applying direct magnetic field exposure before planting and investigates the impact of ultraviolet irradiation on tuber growth and productivity. Signifi cant emphasis was placed on the efficacy of chemical and biological agents in preventing potato scab. The findings show that optimal biometric indicators and potato yields were achieved with a magnetic induction of 30 millitesla. Any deviation from this treatment dose results in reduced biometric indicators and yields, which, however, remain hirer than those of the untreated controls. (Conclusions) The application of fungicidal disinfectants effectively curtails the development of common scab, with the highest efficacy achieved using Rovral Aquafl o 500. Post-treatment with ultraviolet radiation at a dose of 120-240 joules per square meter enhances vegetative growth, productivity, and tuber reproduction rates. The most favorable biometric indicators and yields were observed when a magnetic induction treatment dose of 0.23 joule-seconds per kilogram was applied.